The imperative of sustainable growth and reporting integration. Three eras in the corporate reporting development - Karmańska, Anna (Copernican Journal of Finance & Accounting, 2014)
This article is aimed at the presentation of an opinion in the important discussion about the further development of corporate performance reporting standards, which go far beyond the standards of financial reporting. The current guidelines on social responsibility reporting and the conceptual frameworks of the so-called integrated reporting may give rise to questions on the costs and benefits with regard to corporate reporting within the trend of sustainable growth. The present article, which is the first part of a two-part analysis, discusses synthetically three eras in the corporate development reporting. Their context should determine the perception of the current trend of development corporate reporting made in compliance with the imperative of sustainable growth. The review indicates the premises which appeared to be the driving force of a quality surge in the area corporate performance reporting. There is a conviction expressed in the text that the presently emerging fourth era in the development of corporate reporting will significantly change the conceptual model of this kind of reporting.